Improved SARS-CoV-2 Spike Glycoproteins for Pseudotyping Lentiviral Vectors - Ayoub, Paul G.; Purkayastha, Arunima; Quintos, Jason; Tam, Curtis; Lathrop, Lindsay; Tam, Kevin; Ruiz, Marlene; Hollis, Roger P.; Gomperts, Brigitte N.; Kohn, Donald B. (Frontiers in Virology, 2021)
The spike (S) glycoprotein of SARS-Cov-2 facilitates viral entry into target cells via the cell surface receptor angiotensin-converting enzyme 2 (ACE2). Third generation HIV-1 lentiviral vectors can be pseudotyped to replace the native CD4 tropic envelope protein of the virus and thereby either limit or expand the target cell population. We generated a modified S glycoprotein of SARS-Cov-2 to pseudotype lentiviral vectors which efficiently transduced ACE2-expressing cells with high specificity and contain minimal off-target transduction of ACE2 negative cells. By utilizing optimized codons, modifying the S cytoplasmic tail domain, and including a mutant form of the spike protein, we generated an expression plasmid encoding an optimized protein that produces S-pseudotyped lentiviral vectors at an infectious titer (TU/mL) 1000-fold higher than the unmodified S protein and 4 to 10-fold more specific than the widely used delta-19 S-pseudotyped lentiviral vectors. S-pseudotyped replication-defective lentiviral vectors eliminate the need for biosafety-level-3 laboratories required when developing therapeutics against SARS-CoV-2 with live infectious virus. Furthermore, S-pseudotyped vectors with high activity and specificity may be used as tools to understand the development of immunity against SARS-CoV-2, to develop assays of neutralizing antibodies and other agents that block viral binding, and to allow in vivo imaging studies of ACE2-expressing cells.